Transforming Vocal Education through the Implementation of Score Creator and Cloud-Based E-Learning within the TTIE Framework - A, Heryanto; Wadiyo, Wadiyo; Cahyono, Agus; Suharto (Universitas Pendidikan Ganesha, 2025)
The limited effectiveness of vocal instruction in digital learning contexts presents a challenge in 21st-century arts education. This study aims to explore the effectiveness of integrating the TTIE pedagogical framework (Transfer, Translation, Imitation, Evaluation) in digital-based vocal learning. Employing a qualitative case study approach, the research involved participants from three active vocal communities engaged in online training programs. Data were collected through observation, documentation, and in-depth interviews, and analyzed thematically. The digital platforms used Score Creator and Score Cloud served as visual-auditory tools to support vocal transposition activities and track learner progress. The findings reveal that the TTIE framework significantly enhances pitch accuracy, learner autonomy, and peer collaboration by combining solfeggio-based approaches with digital innovation. The digital tools facilitated formative assessment, peer feedback, and self-reflection, while fostering ethical responsibility in learning. The media also demonstrated adaptability across various learning needs and contexts, making it a scalable model for modern music education. This study concludes that the integration of TTIE within digital platforms improves pedagogical effectiveness and aligns with the demands of personalized, flexible, and technology-driven instruction. The findings contribute to the advancement of digital arts education and offer opportunities for future innovation in music pedagogy.